The Effect Of Green Betel Cook On Pain Reduction And Perineal Wound Healing Process In Postpartum Mothers at BPS Mulyani Perdagangan II village, kec. Bandar. Regency. Simalungun - Kamaliah Ainun; Kristina Kristina (Sean Institute, 2023)
Infection of the birth canal wound can occur because the mother does not pay attention to good personal hygiene, does not understand how to properly care for perineal wounds, does not understand the benefits and goals of perineal wound care, and is not diligent in carrying out postnatal care. Effect of green betel decoction on reducing pain and healing process of perineal wounds in postpartum women at BPS Mulyani DesaTrading II Kec. city. Regency. Simalungun in 2020. This study used a Quasy Experimental Design research type, with a Post Test Only Control Group design. The population in the study were all postpartum mothers from day 1 to day 10 in April-May at BPS Mulyani DesaTrading II Kec. city. Regency. Simalungun in 2020 as many as 25 people, sample using proposive sampling, with research techniques using the Mann-Whitney U-Test as a hypothesis tester. The results of research on perineal wound healing in the group that was given green betel decoction at BPS Mulyani Trading Village in 2020 were the majority normal, namely 6 respondents (60.0%), 3 respondents fast (30.0%) and only 1 respondent slow (10, 0%). Healing of perineal wounds in the group that was not given green betel decoction at BPS Mulyani DesaTrading in 2020 was mostly slow, namely 6 respondents (60.0%), and normal as many as 4 respondents (40.0%), while there was no fast The conclusion is that there is a significant effect of green betel decoction on reducing pain and the process of healing perineal wounds in postpartum women at BPS Mulyani Perdagangan II Regency. Simalungun in 2020